Pengaruh Pendidikan Kesehatan Terhadap Pencegahan Demam Berdarah Dengue (DBD) Pada Anak Usia Sekolah - Suhariati, Hindyah Ike; Ruliati, Ruliati (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
One of the main health problems that occurs in Indonesian society today is dengue hemorrhagic fever (DHF). Mosquito bites of aedes aegypti and aedes albopictus often occur during the rainy season which is the cause of dengue hemorrhagic fever (DHF). Every year the incidence of this disease can appear as well as affect the entire age group. Efforts to eradicate Mosquito Nests (PSN) especially by school-age children is still not optimal. In East Java within a period of nine months, from January to September 2022, there were 8,894 cases of dengue hemorrhagic fever (DHF). The purpose of this study was to analyze the effect of Health Education on the prevention of dengue fever in school-age children in Candimulyo State Elementary School 1. Research design using Quasi Experiment (Pre and Post test design ), in this study there was a treatment group. The population in this study was all school-age children who came from grade 5 at Candimul State Primary School 1, using simple random sampling technique. The sample in this study was 40 children. Analysis of paired data (pre and post test) on dengue prevention variables used Wilcoxon sign rank te test with an error rate (α) of 0.05. The results showed that more than half of dengue prevention before counseling was less than 22 people (56.1%), more than half of the prevention DHF after counseling was given good as many as 22 people (56.1%), wilcoxon test results were obtained p = 0.00 < α (0.05) which means that H1 was accepted and HO was rejected. Conclusions in the study is the effect of health education on the prevention of dengue fever in school-age children at Candimulyo State Elementary School 1.